The Correlation Between Food Hygiene and Sanitation in Food Vendors of Lalapan with Enterobacteriaceae Contamination in Fresh Vegetables - Muhammad Ali Shodikin; Enny Suswati; Bagus Hermansyah; Wiwin Sugih Utami; Dwita Aryadina; Nexia Nevarachell Onny Amirsyah (Jurnal Ilmiah Kesehatan, 2023)
Lalapan is a fresh vegetable usually eat up with rice and other Indonesian dishes. However, fresh vegetables can potentially be contaminated with pathogenic bacteria, such as Enterobacteriaceae, harming consumers if not appropriately processed and cleaned. This study analyzes the correlation between food hygiene and sanitation in food vendors of Lalapan with Enterobacteriaceae contamination in fresh vegetables. It used an analytic observational design with a cross-sectional approach. In addition, the population was food vendors of lalapan in the Sumbersari District, Jember Regency. There were 30 respondents with a consecutive sampling method. Food hygiene and sanitation instrument was an observation sheet according to 16 points stipulated in the Regulation of the Minister of Health of the Republic of Indonesia number 1096/MENKES/PER/VI of 2011. In addition, we tested fresh vegetable samples to analyze Enterobacteriaceae contamination with a microbiological test using Salmonella Chromogenic Agar (SCA) media. Then, data analysis used Fisher's exact test with α=0.05. The observation showed that most respondents had good food sanitation hygiene (76.7%). The microbiological examination indicated 23 vegetable samples (76.7%) were contaminated with Enterobacteriaceae. Statistical analysis using Fisher's exact test Exact obtained p=1.000 (p>0.05). Thus, there was no significant correlation between food hygiene and sanitation in food vendors of lalapan with Enterobacteriaceae contamination in fresh vegetables. In conclusion, hygiene, and sanitation food among food vendors of lalapan do not correlate with Enterobacteriaceae contamination in fresh vegetables. Further research could analyze the vegetable's planting, harvesting, and distribution processes as risk factors for Enterobacteriaceae contamination in fresh vegetables.